Analisa Pengaruh Kehilangan Tekanan terhadap Pengikisan Material Sand Trap Sumur X Lapangan Y - Mira Isabela; Risna Risna; Abdul Gafar Karim; Nijusiho Manik; Yudiaryono Yudiaryono (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Milling operations on the sand trap of Well X, Field Y—a mature field—face reduced cleaning efficiency due to uncertain pressure loss distribution within the Coiled Tubing Unit (CTU) circulation system. This study analyzes the magnitude of pressure losses, maps the specific locations of hydraulic energy depletion, and determines the optimal pump flow rate to establish a safe hydraulic window that prevents lost circulation. The method applied is a mathematical hydraulic analysis covering hydrostatic pressure, bit pressure loss (Pb), annular velocity (AV), and Equivalent Circulating Density (ECD), with sensitivity analysis across three pump flow rates (1.1, 1.2, and 1.3 bbl/min). Results show pressure losses accumulate at three critical points: inside the coiled tubing due to helical buckling, at the junk mill nozzle, and across the Positive Displacement Motor (PDM), which suffers wear from abrasive sand. A flow rate of 1.2 bbl/min (50.4 gpm) proved optimal, yielding an annular velocity of 184.24 ft/min—exceeding the minimum critical limit (>180 ft/min)—while maintaining ECD at 8.534 ppg, safely below the formation fracture gradient.